1986
DOI: 10.1148/radiology.159.2.3961186
|View full text |Cite
|
Sign up to set email alerts
|

Distal femoral epiphysis: normal standards for thickness and application to bone dysplasias.

Abstract: Flattening of the epiphysis of the long bones is seen in several bone dysplasias. It is the hallmark of multiple epiphyseal dysplasia and is an important sign in the diagnosis of spondyloepiphyseal dysplasias, diastrophic dysplasia, and pseudoachondroplastic dysplasia. The goal of this study was to determine norms for the height of the distal femoral epiphysis and to apply these standards to patients with bone dysplasias. Ratios of the distal femoral epiphysis height to both the distal femoral metaphysis width… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0
1

Year Published

1989
1989
2014
2014

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 0 publications
0
9
0
1
Order By: Relevance
“…In our study the values for the distal femur and the FEHMW showed less increase with age than those of the control group, but the flattening of the epiphysis was as described in other skeletal dysplasias. 11 The development of the proximal tibial epiphysis followed a similar pattern, although the deformation and degeneration were less pronounced than in the distal femur. Physeal irregularity and metaphyseal intrusions were also more severe in the distal femur, which may be due to the different anatomy of these growth areas.…”
Section: Discussionmentioning
confidence: 87%
See 3 more Smart Citations
“…In our study the values for the distal femur and the FEHMW showed less increase with age than those of the control group, but the flattening of the epiphysis was as described in other skeletal dysplasias. 11 The development of the proximal tibial epiphysis followed a similar pattern, although the deformation and degeneration were less pronounced than in the distal femur. Physeal irregularity and metaphyseal intrusions were also more severe in the distal femur, which may be due to the different anatomy of these growth areas.…”
Section: Discussionmentioning
confidence: 87%
“…This is probably due to the degenerative changes. Schlesinger et al 11 have described the radiological parameters for the distal femoral epiphysis in bone dysplasias. In our study the values for the distal femur and the FEHMW showed less increase with age than those of the control group, but the flattening of the epiphysis was as described in other skeletal dysplasias.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In such subtle cases, it can be helpful to determine the ratio between the height of the distal femoral epiphyseal and its epiphyseal/metaphyseal width, which is decreased in MED. Values can be compared to established norms [ 108 ]. This dysplasia usually become apparent after 2 years of age, and mild cases can manifest in adulthood merely with relatively short stature.…”
Section: Multiple Epiphyseal Dysplasia (Med)mentioning
confidence: 99%